Detection of cannabis products in urine by radioimmunoassay. Issue 5979 (9th August 1975) - Marks, V; Teale, D; Fry, D
Abstract : A radioimmunoassay specific for the closed, three-ringed cannabinoid nucleus was used to detect and measure caname from hospital inpatients not suspected of taking drugs. None of these contained tetrahydro-cannabinol cross-reacting cannabinoids (THC-CRC). The other 393 specimens were from patients known or suspected to be taking various drugs. Of these 51 out of 162 from one hospital treatment clinic and 19 out of 50 from another were positive for THC-CRC. Out of 107 urine specimens from an independent drug treatment clinic 71 were positive for THC-CRC, as were 13 out of 74 specimens from patients in whom drug misuse was suspected or thought possible.